2021
DOI: 10.1186/s40813-021-00219-w
|View full text |Cite
|
Sign up to set email alerts
|

Using nontargeted LC-MS metabolomics to identify the Association of Biomarkers in pig feces with feed efficiency

Abstract: Background Improving feed efficiency is economically and environmentally beneficial in the pig industry. A deeper understanding of feed efficiency is essential on many levels for its highly complex nature. The aim of this project is to explore the relationship between fecal metabolites and feed efficiency-related traits, thereby identifying metabolites that may assist in the screening of the feed efficiency of pigs. Results We performed fecal metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…WGCNA was originally applied to transcriptomics data, but it has also been recently employed for network generation using metabolomics data from human and human microbiome ( Osterhoff et al, 2014 ; Pedersen and Sofia, 2018 ; Vernocchi et al, 2020 ; Murga-Garrido et al, 2021 ; Petersen et al, 2021 ), animal ( Wu et al, 2021 ), and plants ( DiLeo et al, 2011 ). ( Samal and Martin, 2011 ).…”
Section: Experimental Networkmentioning
confidence: 99%
“…WGCNA was originally applied to transcriptomics data, but it has also been recently employed for network generation using metabolomics data from human and human microbiome ( Osterhoff et al, 2014 ; Pedersen and Sofia, 2018 ; Vernocchi et al, 2020 ; Murga-Garrido et al, 2021 ; Petersen et al, 2021 ), animal ( Wu et al, 2021 ), and plants ( DiLeo et al, 2011 ). ( Samal and Martin, 2011 ).…”
Section: Experimental Networkmentioning
confidence: 99%
“…Pork is one of the most consumed meats in the world and the main source of animal protein for humans. Furthermore, Duroc × (Landrace × Yorkshire) (DLY) commercial pigs dominate the pork market in China ( Wu et al, 2021 ). Among them, Duroc pigs provide half of the genetic contribution in DLY pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The power of metabolomics is that it non-invasively detects subtle phenotypic changes, innate phenotypic propensities, and dietary responses in livestock research, breeding, and assessment through new varieties of bio-samples such as semen, amniotic fluid, saliva, and urine. Wu et al (2021) found that small metabolite profiling of pig feces by LC-MS metabolomics correlated with their feed efficiency and can be used as a reference for selecting animals with high feed conversion efficiency and responsiveness to new feed additives (Wu et al, 2021). Given that fecal metabolome are reflections of intestinal microbiota, cellular metabolism and digestion/absorption of nutrients in the gut (Zierer et al, 2018;Malheiros et al, 2021), the metabolites present in the feces could indicate their feed conversion efficiency (Wu et al, 2021).…”
Section: Metabolomicsmentioning
confidence: 99%
“…Wu et al (2021) found that small metabolite profiling of pig feces by LC-MS metabolomics correlated with their feed efficiency and can be used as a reference for selecting animals with high feed conversion efficiency and responsiveness to new feed additives (Wu et al, 2021). Given that fecal metabolome are reflections of intestinal microbiota, cellular metabolism and digestion/absorption of nutrients in the gut (Zierer et al, 2018;Malheiros et al, 2021), the metabolites present in the feces could indicate their feed conversion efficiency (Wu et al, 2021). Fecal metabolome was also shown to change as a function of stress in beef cattle (Valerio et al, 2020).…”
Section: Metabolomicsmentioning
confidence: 99%